2019
DOI: 10.1177/1120672119832171
|View full text |Cite
|
Sign up to set email alerts
|

Change in cardiac troponin T level after intravitreal anti-vascular endothelial growth factor treatment: Prospective pilot study

Abstract: Background: Evaluate subclinical myocardial injury associated with intravitreal anti-vascular endothelial growth factor therapy by measuring serum high-sensitivity cardiac troponin T. Methods: This is a prospective pilot comparative study conducted at American University of Beirut Medical Center, Beirut, Lebanon. In total, 40 consecutive patients were randomized to receive either intravitreal bevacizumab or ranibizumab. Patients received three consecutive monthly injections of the assigned drug, then continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In a prospective study of 40 patients receiving monthly injections of either intravitreal bevacizumab or ranibizumab, there were no signs of cardiotoxicity as measured by cardiac troponin T levels and a decrease in plasma VEGF levels that correlated with the number of injections. However, the decrease in VEGF levels was only statistically significant in the bevacizumab group at Week 24 [ 17 ].…”
Section: Updates On the Safety And Adverse Effects Of Intraocular Ant...mentioning
confidence: 99%
“…In a prospective study of 40 patients receiving monthly injections of either intravitreal bevacizumab or ranibizumab, there were no signs of cardiotoxicity as measured by cardiac troponin T levels and a decrease in plasma VEGF levels that correlated with the number of injections. However, the decrease in VEGF levels was only statistically significant in the bevacizumab group at Week 24 [ 17 ].…”
Section: Updates On the Safety And Adverse Effects Of Intraocular Ant...mentioning
confidence: 99%
“…Anti-VEGF therapy is also widely recommended to maintain visual functioning in patients with age-related macular degeneration, retinal vein occlusion, myopic choroidal neovascularization, and DME [ 1 , 2 ]. Large clinical studies [ 3 – 6 ] have confirmed the safety of anti-VEGF therapy, but some meta-analyses [ 7 ] indicate a high risk of systemic adverse events after repeated intravitreal anti-VEGF therapy for DME. This inconsistency may result from the study design strategy because large studies are often limited to patients with relatively fewer and minor complications and exclude patients at risk for the worst adverse events such as cerebrovascular and arteriothrombotic events [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%